Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557186
|View full text |Cite
|
Sign up to set email alerts
|

I can wait a minute

Abstract: Public displays have advanced from isolated and non interactive "ad" displays which show images and videos to displays that are networked, interactive, and open to a wide variety of content and applications. Prior work has shown large potential of user-generated content on public displays. However, one of the problems with user-generated content on public displays is moderation as content may be explicit or troublesome for a particular location. In this work we explore the expectations of users with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The authors developed and deployed a web-based application on a display located on the university campus that allowed students to tweet images to the display that were shown after a short delay introduced by the moderation process. We believe that both [15] and [11] are examples that express the potential of increasing the value of displays to viewers by delivering more relevant content -our deployment follows in this pattern by having users of the system (students) contribute to content generation to increase relevance.…”
Section: Memory Augmentation In Other Domainsmentioning
confidence: 96%
See 2 more Smart Citations
“…The authors developed and deployed a web-based application on a display located on the university campus that allowed students to tweet images to the display that were shown after a short delay introduced by the moderation process. We believe that both [15] and [11] are examples that express the potential of increasing the value of displays to viewers by delivering more relevant content -our deployment follows in this pattern by having users of the system (students) contribute to content generation to increase relevance.…”
Section: Memory Augmentation In Other Domainsmentioning
confidence: 96%
“…The results show that participants considered public displays as the most appropriate medium for posting and viewing news and events, similar to the kinds of content that could also be found on social media pages of communities. In a further example, Greis et al [11] investigated viewer expectations of content moderation delays for user generated content. The authors developed and deployed a web-based application on a display located on the university campus that allowed students to tweet images to the display that were shown after a short delay introduced by the moderation process.…”
Section: Memory Augmentation In Other Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Should unknown content be introduced into the network, all expected that moderation would be required. Greis et al [38] found that passers-by also expect content pre-moderation, and would be prepared to wait for up to 10 minutes for their content to be approved. However, their in-the-wild deployment found that pre-moderation significantly lowered the number of content items posted.…”
Section: Openness and Controlmentioning
confidence: 99%
“…Given the above, we formulate three further requirements to support open display networks: [38] proposes community-based flagging of inappropriate content, or at least to provide information on how content is moderated and how long the average wait should be. As an alternative, Davies et al [24] propose the use of trusted applications that offer their own moderation.…”
Section: Openness and Controlmentioning
confidence: 99%